Chronic Depression Alters Mothers’ DHEA and DEHA-to-Cortisol Ratio: Implications for Maternal Behavior and Child Outcomes - Apter-Levy, Yael; Zagoory-Sharon, Orna; Feldman, Ruth (Frontiers in Psychiatry, 2020)
Maternal depression is a common complication of pregnancy and a major public health problem. In recent years advances have been made in understanding the underlying mechanisms of this condition and research has pointed to the crucial role of the HPA axis in this disorder. However, most studies focused on cortisol expression and regulation while recent attention has shifted to include the sulfate steroids DHEA and DHEA-S. Using an extreme-case design, a community cohort of 1983 women with no comorbid risk was recruited at birth and depression was assessed periodically across the first postpartum year. At six years, 156 families were re-visited: 46 mothers were defined as chronically-depressed and 103 controls reported no depression from birth to six. Mothers and children were diagnosed by structured psychiatric interviews and mother-child interactions were observed. Maternal diurnal cortisol (CT) and dehydroepiandrosterone (DHEA) were assessed. Depressed mothers had lower levels of DHEA (AUCg), flattened DHEA diurnal variability (AUCi), and smaller DHEA-to-CT Ratio. Regression analysis demonstrated that maternal sensitivity during mother-child interaction was independently predicted by maternal depression, DHEA levels, child CT, and child social withdrawal. Results underscore the need for multi-level understanding of the dynamic interplay between maternal psychopathology, mother-child relationship, and pituitary–adrenal-cortex-to-medulla balance in studying the cross-generation transfer of psychiatric vulnerability from depressed mothers to their children.